ATIVIDADE DO FUNGO Beauveria bassiana (BALS.-CRIV.) VUILL. (ASCOMYCETES:HYPOCREALES) ISOLADO UNIOESTE 76 CONTRA OVOS E NINFAS DE Euschistus heros (FABRICIUS, 1798) (HEMIPTERA: PENTATOMIDAE) E SUA INFLUÊNCIA SOBRE PARÂMETROS BIOLÓGICOS DE Telenomus podisi ASHMEAD, 1893 (HYMENOPTERA: SCELIONIDAE) - Alvim, Paulo Wesley (2024)
Soy is one of the world's primary agricultural commodities, with significant production in Brazil. However, like other crops, soy faces considerable challenges, such as losses caused by the brown stink bug, Euschistus heros, which is currently considered a major pest. This insect causes substantial damage by feeding on the plant from its early stages. The main method of controlling this pest is the use of chemical insecticides, which, besides their limited effectiveness, have resulted in a series of environmental, ecological, and even public health consequences. To mitigate this situation, integrated pest management (IPM) is gaining prominence, with an increasing focus on biological control as a more sustainable alternative. In this context, the fungus Beauveria bassiana stands out as an efficient pest control agent. Through selection studies, new isolates are discovered. The previously selected isolate Unioeste 76 shows high virulence against the brown stink bug and high production yields. Another promising approach for pest control is the use of the egg parasitoid Telenomus podisi. However, it is necessary to verify the safety of newly selected fungus isolates to these natural enemies. The objective of this work was to verify the activity of the B. bassiana isolate Unioeste 76 against eggs and nymphs of E. heros and its effects on the biological parameters of the parasitoid T. podisi. On viable E. heros eggs, 0.2 mL of pure conidia suspension (CP), oil dispersion formulation (OD), both at 1×10^9 conidia/mL, and vegetable oil emulsion (EV 1%) were applied. In the control group, distilled water with Tween 80 was used. For third and fifth instar nymphs, 1 mL of the CP and OD treatments, both at concentrations of 1×10^7, 1×10^8, and 1×10^9 conidia/mL, and EV 1% and the control group were sprayed. The effect on the parasitoid was evaluated with non viable brown stink bug eggs, grouped on paper cards. The eggs received 0.2 mL of the CP treatments at 1×10^7, 1×10^8, 1×10^9, and 1×10^10 conidia/mL and OD at concentrations of 1×10^7, 1×10^8, and 1×10^9 conidia/mL, as well as EV 1% and the control group. After application and drying, the egg cards were offered to the parasitoid T. podisi in choice and no-choice tests. Another group of previously parasitized eggs received the same treatments. After 12 days of incubation (26 ± 2°C, 60% ± 10% RH, and photoperiod L12), the absence of ovicidal effect was observed, and a reduction in the survival rate of newly hatched E. heros nymphs was noted, reaching cumulative mortality from 76.7 to 93.8%, with a survival rate reduction of 75% between 6 to 11 days. Third instar nymphs, after contact with the fungus, showed cumulative mortality from 27 to 70%, and a survival rate reduction of 50% in 9 to 20 days. For fifth instar nymphs, mortality varied from 48% to 91%, with a survival rate reduction of 75%, between 6 to 11 days, at the highest concentrations. The fungus at concentrations of 1×10^7, 1×10^8, and 1×10^9 conidia/mL did not cause alterations in the analyzed parameters of the parasitoid (egg-adult period, parasitism, sex ratio, and emergence). However, alterations were 11 observed with the 1% vegetable oil emulsion and formulated conidia. Similarly, alterations in parasitism, mortality, and reduction in the parasitoid survival rate were observed only in the treatment with conidia suspension at the concentration of 1×10^10 conidia/mL. Thus, it is concluded that the B. bassiana isolate Unioeste 76 has potential for controlling the brown stink bug even at the nymph stage, besides being compatible and safe, at recommended concentrations, to the parasitoid T. podisi.